Legal Protection for People with Disabilities in the Making of Authentic Notary Deeds - Nor Hariani, Dea; Hanim, Lathifah (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Legal protection for persons with disabilities in the making of authentic deeds is an important issue in notarial practice in Indonesia. Although constitutionally every citizen has equal status before the law as specified in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia, in practice persons with disabilities still face various obstacles in accessing legal services, particularly in the making of authentic deeds before a notary. These obstacles arise from regulatory, technical, and cultural aspects, especially concerning formal requirements such as signing the deed, the use of sign language interpreters for the deaf, and the reading of the deed for the blind. This research employs a normative legal research method. The approaches used are the statute approach, the conceptual approach, and the case approach by examining the Supreme Court Decision Number 121 K/Pdt/2016 as the main secondary legal material. The type of data used is qualitative with secondary data obtained through literature study, while data analysis was carried out descriptively and analytically. The results of the research indicate that the legal status of persons with disabilities in the making of authentic deeds has not been optimally protected due to normative gaps in the Notary Law, which does not explicitly regulate reasonable accommodation. Supreme Court Decision Number 121 K/Pdt/2016 affirms that physical limitations do not eliminate the legal capacity of persons with disabilities, thereby confirming their right to conduct legal acts. The decision has become progressive jurisprudence that provides substantive legal protection, promotes inclusive notarial practices, and aligns with Law Number 8 of 2016 on Persons with Disabilities, the principles of justice in Islam, and Social Justice as enshrined in Pancasila.